The concept of the principle of subsidiarity in EU law - Stetsiv, R. S. (Науковий вісник Ужгородського національного університету. Серія Право, 2025)
The article examines the principle of subsidiarity as one of the key legal and political principles of the functioning of the European Union. The origin of this concept, which has its roots in Christian social doctrine, in particular in Catholic social teaching, is investigated. Here, subsidiarity was defined as a principle regulating the distribution of responsibility between the individual, the community and the state. In the EU legal system, subsidiarity acts as a mechanism for determining the optimal ratio of powers between the supranational institutions of the Union and the Member States, ensuring a balance between integration and the preservation of sovereignty. The article examines the regulatory framework that enshrines the principle of subsidiarity, including the Single European Act, the Maastricht and Amsterdam Treaties, Protocol No. 2 on the principles of subsidiarity and proportionality and the Lisbon Treaty. Special attention is paid to the difference between the concepts of negative and positive subsidiarity, as well as the ways of interpreting this principle in the theory of EU law. Attention was paid to the role of the Court of Justice of the EU in the development of the practice of applying subsidiarity, analyzing key court decisions that illustrate the difficulties of applying this principle in the context of the expansion of the Union’s competences. It is noted that although the Court of Justice of the EU usually applies a restrained approach to monitoring compliance with subsidiarity, its consolidation as a legally binding principle contributes to the formation of institutional dialogue between Member States and Union bodies. Particular attention is paid to the prospects for using the principle of subsidiarity in the process of legal integration of Ukraine into the EU. The article argues that the effective implementation of this principle can become an important tool for harmonizing Ukrainian legislation with European law, while ensuring the preservation of national legal specificity.